Optimización del plan de mantenimiento preventivo para moldes de inyección de preforma en Iberplast S.A.S. (2021)
The development of this project aims to optimize the current preventive maintenance plan executed in the preform injection molds at Iberplast S.A.S; company that produces preforms for the beverage sector. Currently the most important productive area in the company is the production of preforms, due to the high demand for work in Husky molds it is necessary to consider a reduction in the time required for maintenance and an increase in the efficiency of the maintenance plan, intervening in the activities developed, evaluating their order, execution times, human resources, instrumental resources, among others; To determine the adjustments that will be made within the current preventive maintenance plan, it will be necessary to review the maintenance history, collect information on the critical points of availability of the mold, in the same way information on the technical sheet of each mold in order to contemplate in a way broader operation of each mold and the recommendations that the manufacturer has regarding the mold of each family (GPET, HyPET and HPP).